Myoclonic Absence Seizures and Chromosome Anomalies - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1998)
The relation between myoclonic absence-like seizures (MAS) and underlying chromosome disorders was evaluated in 14 patients at three centers in Italy.